The Synthesis and Characterization of Bemotrizinol Impurities - Thorat, Dattatray; Bhattacharya, Anwesha; Patil, Sandip; Singh, Anoop; Nighot, Dnyaneshwar; Awasthi, Pramod Kumar (Orbital: The Electronic Journal of Chemistry, 2025)
Bemotrizinol (Bis-Ethylhexyloxyphenol Methoxyphenyl Triazine) is widely used ultraviolet filter in sunscreens and cosmetics, is critical for effective UV protection. However, the presence of impurities in bemotrizinol can impact both its efficacy and safety. Regulatory guidelines such as ICH Q3A(R2) and Q3B(R2) emphasize the identification and control of impurities in active pharmaceutical ingredients (APIs) to ensure safety, efficacy, and product quality. This study investigates the elaborate procedures for the synthesis of six impurities related to bemotrizinol. The synthetic methodologies for these impurities were not documented previously in the literature. Our findings reveal significant insights into the quality control of bemotrizinol to ensure product safety and efficacy. The results of this study provide valuable insight into the impurity profile of Bemotrizinol. These findings also contribute to regulatory compliance by enabling proper identification of impurities.